An advanced medium-entropy substituted tunnel-type Na0.44MnO2 cathode for high-performance sodium-ion batteries. Issue 3 (4th January 2023) - Chen, Jiawu; Hou, Zhiguo; Zhang, Lei; Mao, Wutao; Zhang, Tianwen; Zhang, Xueqian; Qian, Yitai
Abstract : NMO-1 exhibits good electrochemical performance, with a capacity retention of more than 80% after 2000 cycles at a rate of 10C between 2 and 4 V. The suggested approach of medium-entropy substitution offers insight into the design of high-energy Na-ion cathode materials. Abstract : Because of the irreversible reaction and sluggish migration rate of Na ions during the electrochemical process, the cycling stability and rate capability of tunnel-type Na0.44 MnO2 are poor. In this work, it is discovered that medium-entropy substitution can significantly increase cycling stability and rate capability. The prepared cathode Na0.44 Mn0.97 Al0.01 Ti0.01 Co0.01 O2 exhibits an enhanced rate capability of 80 mA h g −1 at 20C and demonstrates a high discharge capacity of 78 mA h g −1 after 2000 cycles at 10C, with a high capacity retention of approximately 80%. The mechanism of the improved electrochemical performance of Na0.44 MnO2 by the medium-entropy substitution strategy is deeply studied. The medium-entropy substitution increases the spacing of lattice fringes and replaces manganese, resulting in improved rate capability and cycling performance of Na0.44 MnO2 . The discovered medium-entropy Na0.44 MnO2 material provides new insight into the development of tunnel-type electrode materials and promotes their application in rechargeable Na-ion batteries.